Pedagogical principles and methods underpinning education of health and social care practitioners on experiences and needs of older LGBT+ people: Findings from a systematic review. (October 2019) - Higgins, Agnes; Downes, Carmel; Sheaf, Greg; Bus, Elisa; Connell, Sandra; Hafford-Letchfield, Trish; Jurček, Anže; Pezzella, Alfonso; Rabelink, Irma; Robotham, George; Urek, Mojca; van der Vaart, Nina; et al.
Abstract: Background: There is a growing awareness of the need for LGBT + competency training to ensure that the health and social care services offered to older LGBT + people is affirmative and gender sensitive. Objective: To conduct a synthesis of the literature that describes the pedagogical principles, curriculum content and methods (teaching and assessment) used to educate health and social care practitioners on the experiences and needs of older LGBT + people. Design: Systematic thematic review of literature. Data sources: MEDLINE, CINAHL, PsycINFO, EMBASE, Web of Science, Social Sciences Index, ERIC. Method: In accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) Statement, this review examined peer-reviewed papers published in English, prior to April 2018 that addressed pedagogical and curriculum issues on the inclusion of needs and experiences of older LGBT + people. Results: The combined searches yielded 2214 papers of which 17 papers were eligible for inclusion, 10 discussion papers and 7 evaluation studies. Analysis identified the following themes: i) Acknowledging the wider historical context of older LGBT + people's lives; ii) Recognising that older LGBT + people are not a homogenous group; iii) Incorporating a multitude of theories and models from different perspectives; iv) Alerting practitioners to the health issues and disparities facing older LGBT + people; v) Including content that supports inclusive care for older LGBT + people; vi) Addressing barriers to older LGBT + people accessing health care; vii) Interactive activities are the preferred pedagogical strategy; viii) Involving older LGBT + people in curriculum development is a core principle; and ix) Mandatory education is not always the solution. Conclusion: As the field matures there is a need for more exploration of curriculum principles, assessment strategies and strategies to overcome barriers to the inclusion of issues experienced by older LGBT + people within curricula.